2017
DOI: 10.1080/1369183x.2017.1315849
|View full text |Cite
|
Sign up to set email alerts
|

Asian migration and education cultures in the Anglo-sphere

Abstract: Asian migration is transforming education cultures in the Anglosphere. This is epitomised in the mounting debates about 'tiger mothers' and 'dragon children', and competition and segregation in schools. Anxiety and aspiration within these spaces are increasingly ethnicised, with children of Asian migrants both admired and resented for their educational success. This paper presents some frameworks for understanding how Asian migration both shapes and impacts upon education outcomes, systems and cultures, focusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…bearers of a culture, located within a boundaried world, which defines them and differentiates them from others" (Grillo 2003, 158). Using cultural essentialism in othering means that certain attributes or behaviours that are ascribed to a cultural group are viewed as being inherent and static, whereby they appear independent of the context (Watkins, Ho andButler 2017, 2284).…”
Section: Theoretical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…bearers of a culture, located within a boundaried world, which defines them and differentiates them from others" (Grillo 2003, 158). Using cultural essentialism in othering means that certain attributes or behaviours that are ascribed to a cultural group are viewed as being inherent and static, whereby they appear independent of the context (Watkins, Ho andButler 2017, 2284).…”
Section: Theoretical Approachmentioning
confidence: 99%
“…The data at hand shows forms of positive othering that ascribe specific care qualities to 'refugees'. This interpretation pattern on 'refugees'' ability to provide family-like care may be analysed as cultural essentialism according to Grillo (2003) and Watkins et al (2017), because in a homogenising way it is assumed that 'refugees' are defined by their ascribed culture intermingled with religion, which is viewed as inherent and static. Therefore, in this interpretation it is ascribed to the cultural background of 'refugees' to provide high-quality (basic) care for the elderly, while structural pressures on these persons are neglected, such as the requirement to undertake an apprenticeship to gain a residence permit.…”
Section: The Construction Of a Culture-specific Relation Of Respect Fmentioning
confidence: 99%
“…For Australia, this would be generally true of students with African, Middle Eastern and Pacific language backgrounds. Socioeconomic explanations may also work in the other direction because of Australia's points‐based immigration scheme; the stronger performance of students from East and Southeast Asia may be because their parents are professionals or have sizable assets (Watkins, Ho, & Butler ). For the United States, Lee and Zhou () dismiss the role of cultural factors in “Asian academic excellence” and point to the immigration policy of allowing entry of highly educated Asian immigrants.…”
Section: Introductionmentioning
confidence: 99%
“…Research has consistently shown that children of new Chinese immigrants, or xinyimin, 1 generally do better in school than their native peers, as measured by GPA, grades, college attendance, and college graduation institutions, in countries such as the United States, Canada, the U.K., Australia, New Zealand, and Singapore (Abada et al 2008;Archer and Francis 2006;Chung et al 1997;Ho 2017;Kasinitz et al 2009;Lee and Zhou 2015;Seah 2017;Sue and Okazaki 1990;Watkins et al 2017). And their extraordinary academic success is often attributed to Confucian heritage culture or "tiger mom" parenting, the traditional Chinese way of childrearing of a strict and disciplinarian mother (Chua 2011;Chua and Rubenfeld 2014).…”
Section: Introductionmentioning
confidence: 99%